Moving the Production Line - A Successful Structured Approach - Ismail, Mostafa; Allam, Mohammed (Journal of Global Economy, Business and Finance, 2025)
This paper presents a comprehensive approach to relocating and consolidating manufacturing lines and process equipment between plants efficiently and methodically. As global trends shift manufacturing operations from one region to another, the traditional AS IS Lift and Shift method often falls short in optimizing the manufacturing process. The proposed approach emphasizes redesigning and improving manufacturing processes to eliminate waste and enhance efficiency using advanced technologies combined with lean principles. This method promises significant benefits, including reduced lead times, improved quality, and lower manufacturing costs. The process is broken down into three main workstreams: Industrial and Manufacturing Engineering Planning, Production Control and Logistics Engineering Planning, and Program Management Support. Each workstream comprises detailed phases and steps that ensure a seamless transition. The paper highlights the importance of redesigning manufacturing processes, detailing decommissioning coordination at the origin plant, integrating and testing manufacturing processes at the target plant, and providing ongoing support during the manufacturing build and launch phase. Additionally, it underscores the need for meticulous logistics planning and robust program management to manage stakeholders, delivery, change, and risks effectively. Future work will explore integrating augmented, virtual, and mixed reality technologies to enhance planning, execution, and validation processes for even smoother transitions.